Fertilizer derived from alkaline hydrothermal alteration of K-feldspar: A micrometer to nanometer-scale investigation of K in secondary reaction products and the feldspar interface. (March 2021) - Zhai, Yuanyuan; Hellmann, Roland; Campos, Andrea; Findling, Nathaniel; Mayanna, Sathish; Wirth, Richard; Schreiber, Anja; Cabié, Martiane; Zeng, Qingdong; Liu, Shanke; Liu, Jianming
Abstract: Global food security concerns have spurred increasing demand for locally sourced and produced K-fertilizers. Various processes have been explored for more than a century; one promising solution is based on the alkaline aqueous alteration of feldspar-rich rocks at elevated temperatures. However, knowledge of the overall physico-chemical reactions comprising dissolution of feldspar and precipitation of secondary phases is still rudimentary, in particular how the feldspar structure evolves at the nm-scale during hydrolysis at alkaline conditions. Here we report on the results of a study aimed at converting potassium feldspars to K-rich fertilizer based on the alteration of sanidine and microcline samples at 190 °C in pH 12 Ca(OH)2 solutions for 24 h. Based on X-ray diffraction and Rietveld refinement, the secondary authigenic minerals that precipitated are primarily composed of Ca-carbonate (calcite, vaterite), and Ca-(Al)-silicates, such as tobermorite and hydrogrossular. Short-term bench top leaching experiments in water prove that the hydrothermal product releases up to two orders of magnitude more K than the unaltered K-feldspar starting material, pointing to its application as a ready-to-use fertilizer for K-deficient soils. Detailed chemical mapping and energy dispersive X-ray spectroscopy (FESEM- and TEM-EDXS) analyses of the precipitates at the μm to nm-scale show that the distribution of K associated with the secondary phases is very heterogeneous, both spatially and in terms of concentrations. Using various analytical transmission electron microscopy (TEM) techniques, e.g., HRTEM, TEM-EDXS, EFTEM, to investigate the structure and chemistry of the feldspar interface, we find no evidence for a change in chemistry or structure at the nm-scale, even though dissolution continuously decreases the volume of each grain. Our observations also show the existence of an amorphous surface altered layer (SAL) of variable thickness (10–~100 nm) forming at the feldspar interface. Nanometer-scale chemical measurements show that this amorphous SAL is rich in K, and therefore may also be an important reservoir of easily leachable K. We hypothesize that it forms continuously and in situ at the expense of the feldspar by a coupled interfacial dissolution-reprecipitation process (CIDR). Highlights: Alkaline hydrothermal alteration of K-feldspars yields K-fertilizer for soils. SEM and TEM techniques used to measure [K] in secondary phases and interface. Labile K in hydrothermal product associated with soluble secondary phases. The K-feldspar structure dissolves stoichiometrically, with no change in chemistry. Coupled interfacial dissolution-reprecipitation (CIDR) controls dissolution process.